A retrospective cohort study of bleeding characteristics and hidden blood loss after segmental pedicle screw instrumentation in neuromuscular scoliosis as compared with adolescent idiopathic scoliosis - Soini Venla; Raitio Arimatias; Helenius Ilkka; Helenius Linda; Syvänen Johanna (Elsevier Inc., 2022)
Background
Progressive scoliosis in neuromuscular patients often requires a long instrumented spinal fusion. Previous studies have shown larger intraoperative blood loss in these patients than those with adolescent idiopathic scoliosis (AIS), but the total blood loss composed of visible and hidden blood loss has not been described in this patient population. The aim of our study was to investigate the bleeding characteristics and hidden blood loss related to spinal fusion in neuromuscular scoliosis (NMS) as compared to AIS patients.
Methods
A retrospective cohort study with prospective data collection of NMS patients undergoing segmental pedicle screw instrumentation at a university hospital between 2009 and 2021. A comprehensive statistical analysis was performed regarding intra- and postoperative blood loss compared to patient characteristics such as age and diagnosis. Hidden blood loss was estimated and compared to the total blood loss. We standardized amount of bleeding with patient weight and fusion level for further analysis. Consecutive AIS patients served as a control population. Eighty-one consecutive patients with NMS (mean age 15.2 years, 37 females) were included and their bleeding characters were compared with 199 AIS patients (mean age 15.8 years, 143 females). The primary outcome was total blood loss including intraoperative, 24-hour drain output and hidden blood loss. Secondary outcome measures included requirement for blood transfusion.
Results
Neuromuscular patients had a significantly larger total blood loss with mean values of 1914 mL in the NMS and 1357 mL in the AIS groups, respectively (p<0.001). The hidden blood loss was also significantly larger in NMS than in AIS group (566 ± 533 mL vs. 398 ±411 mL, p=0.0332). Neuromuscular scoliosis was also associated with significantly greater weight and levels of fused adjusted intraoperative bleeding (1.79 ml/kg/fused level in NMS vs. 0.87 ml/kg/fused level in AIS vs. p< 0.0001) and hidden blood loss (1.00 ml/kg/levels fused vs. 0.65 ml/kg/fused levels, p=0.053). NMS diagnosis was also a risk factor for greater hidden blood loss in multivariable analysis (p=0.0011). 24-hour drain output was similar in the NMS and AIS groups. Male gender was a risk factor for greater hidden blood loss in the NMS group (p=0.0429). Fifty-nine (73%) NMS and 27 (14%) AIS patients received allogenic red blood cell infusions perioperatively (p<0.001).
Conclusions
Hidden blood loss constitutes one-third of total blood loss in children undergoing segmental pedicle screw instrumentation for neuromuscular scoliosis. Hidden blood loss is significantly greater in the neuromuscular as compared with idiopathic scoliosis. Hidden blood loss should be considered in the perioperative management of NMS.